2012
DOI: 10.1007/s00784-012-0795-0
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of digital models obtained by direct and indirect data capturing

Abstract: Within the limitations of this study, the method of direct digitalisation seems to have the potential to improve the accuracy of impressions for four-unit FDPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
261
2
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(293 citation statements)
references
References 11 publications
7
261
2
23
Order By: Relevance
“…This system also comes with the need for powdering the tooth surface. This intraoral scanner can offer comparable results like conventional methods, regarding accuracy [33]. However, a number of computer-aided impression systems do not require the use of an opaque powder, such as iTero, cara Trios, and CEREC Omnicam [34].…”
Section: Introductionmentioning
confidence: 99%
“…This system also comes with the need for powdering the tooth surface. This intraoral scanner can offer comparable results like conventional methods, regarding accuracy [33]. However, a number of computer-aided impression systems do not require the use of an opaque powder, such as iTero, cara Trios, and CEREC Omnicam [34].…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] A recently introduced method allows the quantitative and qualitative 3D analysis of dental materials, including restorations, impressions, or casts. 19 The aim of this study was to identify the discrepancy, accuracy, and reproducibility of digital casts compared with a master model.…”
mentioning
confidence: 99%
“…The differences in the current results may be attributed to the use of different conventional impression materials and procedures and to different digital impression methods. Guth et al 17 reported that the intraoral Lava C.O.S system showed significantly higher accuracy than the conventional impression procedure and indirect digitalization. However, intraoral conditions such as saliva, powder, and limited space could contribute to inaccuracies in the digital scan.…”
mentioning
confidence: 99%
“…Buna göre; istenilen restorasyon için hazırlanan dişler ağız içi görüntüleme sistemleri yardımı ile taranır ve bilgisayar ortamına aktarılır. 25 Hassasiyet bakımından indirek teknik, konvansiyonel ölçü materyallerini ve ölçü tekniklerini içerdiğin-den direk tekniğe göre farklılıklar göstermektedir. Bu nedenle; ölçü maddelerinin boyutsal stabilitesi, saklama koşulları, dezenfeksiyon sırasındaki distorsiyonlar, ölçü kaşığından ayrılması ve uyumsuzluğu, dental laboratuvara transferi sırasındaki şartlar dikkate alınmalıdır.…”
Section: Direk Teknikunclassified